The Effect of H2SO4 Concentration and Micro Wave Power in Microwave Assisted Hydrolysis of Furfural Production from Empty Palm Fruit Bunches - Kusyanto, Kusyanto; Rahmadina, Suci (Jurnal Bahan Alam Terbarukan, 2019)
Empty fruit bunches (EFB), which are wastes from fresh palm fruit bunches, are one of organic wastes from palm oil processing industries as much as 23% of the total production. The utilization of this waste, which has a high economic value, is still not optimum although it has been used as a boiler fuel. In fact, EFB has a high economic value if processed further. The EFB as a waste can be processed using hydrolysis method to obtain its pentosan content and changed into furfural with the addition of acid as a catalyst. The objectives of this research are to find out the optimum yield on the sulfuric acid concentration and the effects of the power of microwaves used on hydrolysis process of EFB. On this hydrolysis process, 10 grams of Ã‚Â EFB was added with 250ml of sulfuric acid with the variations of 3%, 6%, 9%, 12%, 15%, and 18%, and microwave was used with the power variations of 400W, 600W, and 800W for 75 minutes. The analysis method used in this study to determine the furfural contentis Gas Chromatography (GC). The results showed the highest furfural content was obtained at H2SO4concentration of 9% with 800W power on the microwave and the concentration of 0.39 mg/mL and furfural yield of 0.9620%.Ã‚Â